THE COMMUNICATION STRATEGY OF THE INDONESIAN BOOK PARTY COMMUNITY IN FRAMING SOCIAL ISSUES AND MANAGING PUBLIC IMAGE ON INSTAGRAM - Suci Rachma Praditi; Indah Fajar Rosalina; Wina Puspita Sari; Abdul Kholik; Asep Soegiarto (Indonesian Journal of Islamic Communication, 2025)
This study explores the communication strategy of the Indonesia Book Party (IBP) community in framing social issues and maintaining its image through Instagram. Using a descriptive qualitative method, the research involved in-depth interviews with key IBP members in charge of public relations, risk management, social media, and visual design. The findings reveal that IBP’s strategy is rooted in literacy values, combining reflective narratives with light and engaging visual content. IBP frames social and political issues—such as economic inequality or governmental control—by linking them to literary references, thereby offering critical yet accessible perspectives. Their Instagram presence is strengthened through consistent visual identity, strategic use of memes, inclusive tone, and professional content approval procedures. Audience engagement is fostered via interactive features such as comments, polls, and participatory campaigns. IBP also implements crisis communication protocols to respond empathetically to criticism while maintaining neutrality. This strategy not only helps preserve IBP’s image as a reflective and inclusive literacy community but also encourages the development of a digital literacy culture among followers. Through a balance of aesthetic consistency, value-based communication, and active audience participation, IBP demonstrates how social media can be used as a platform for critical discourse and community building. The study provides a valuable model for digital community management and highlights the potential of Instagram as a tool for educational and social transformation.